2017
DOI: 10.1038/s41598-017-03881-9
|View full text |Cite
|
Sign up to set email alerts
|

The down-regulation of SLC7A11 enhances ROS induced P-gp over-expression and drug resistance in MCF-7 breast cancer cells

Abstract: Adriamycin (ADR) induces the over-expression of P-glycoprotein (P-gp) and multiple drug resistance in breast cancer cells. However, the biochemical process and underlying mechanisms are not clear. Our previous study revealed that ADR increased reactive oxygen species (ROS) generation and decreased glutathione (GSH) biosynthesis, while N-acetylcysteine, the ROS scavenger, reversed the over-expression of P-gp. The present study showed that ADR inhibited the influx of cystine (the source material of GSH) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 43 publications
3
42
0
Order By: Relevance
“…RNA sequencing analysis has revealed that SLC7A11 is upregulated in brain metastatic breast cancer tissues, implying a role for SLC7A11 in breast cancer metastasis [314]. In 2017, Ge et al reported that downregulation of SLC7A11 could confer adriamycin resistance to MCF-7 breast cancer cells by over-expressing P-gp-mediated increased ROS level [315]. In 2018, Bolli et al showed that inhibition of xCT by virus-like-particle immunotherapy could reduce the metastatic potential of breast cancer stem cells [316].…”
Section: Slc7a11 In Breast Cancermentioning
confidence: 99%
“…RNA sequencing analysis has revealed that SLC7A11 is upregulated in brain metastatic breast cancer tissues, implying a role for SLC7A11 in breast cancer metastasis [314]. In 2017, Ge et al reported that downregulation of SLC7A11 could confer adriamycin resistance to MCF-7 breast cancer cells by over-expressing P-gp-mediated increased ROS level [315]. In 2018, Bolli et al showed that inhibition of xCT by virus-like-particle immunotherapy could reduce the metastatic potential of breast cancer stem cells [316].…”
Section: Slc7a11 In Breast Cancermentioning
confidence: 99%
“…SLC7A11 is associated with treatment resistance in breast cancer. Adriamycin suppresses SLC7A11 activity and causes overexpression of reactive oxygen species (ROS)-induced P-glycoprotein, resulting in drug resistance [ 63 ]. SLC7A11 is also responsible for distant metastasis of breast cancer.…”
Section: Amino Acid Transporters In Breast Cancermentioning
confidence: 99%
“…A previous study revealed that high levels of MDR1 and P-gp were associated with chemotherapy sensitivity, high-grade tumors, lymph node metastasis, a poor response and a shorter survival ( 25 ). Ge et al stated that ADM induced the overexpression of P-gp in breast cancer cells, which, in turn, increased the intracellular efflux of ADM ( 26 ). The present study further highlighted that K562/ADM cells were more resistant to ADM, which may provide new insight into leukemic therapies.…”
Section: Discussionmentioning
confidence: 99%